2017
DOI: 10.1186/s13578-017-0135-9
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-let-7c-5p augments enterovirus 71 replication through viral subversion of cell signaling in rhabdomyosarcoma cells

Abstract: BackgroundHuman enterovirus 71 (EV71) causes severe hand, foot and mouse disease, accompanied by neurological complications. During the interaction between EV71 and the host, the virus subverts host cell machinery for its own replication. However, the roles of microRNAs (miRNAs) in this process remain obscure.ResultsIn this study, we found that the miRNA hsa-let-7c-5p was significantly upregulated in EV71-infected rhabdomyosarcoma cells. The overexpression of hsa-let-7c-5p promoted replication of the virus, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…MAP4K4 contains a let - 7 target site in its 3′-UTR, indicating that let-7 family can regulate MAPK pathways by altering MAP4K4 expression levels 39 , 40 . Hsa-let-7c-5p can facilitate human enterovirus 71 replication by inhibiting MAP4K4 expression; this mechanism might explain the virus’s ability to subvert the JNK pathway 41 . Previous studies have demonstrated that ERK1/2 MAPK negatively regulates let-7 by inducing LIN28 expression through Myc transcription 42 .…”
Section: Discussionmentioning
confidence: 99%
“…MAP4K4 contains a let - 7 target site in its 3′-UTR, indicating that let-7 family can regulate MAPK pathways by altering MAP4K4 expression levels 39 , 40 . Hsa-let-7c-5p can facilitate human enterovirus 71 replication by inhibiting MAP4K4 expression; this mechanism might explain the virus’s ability to subvert the JNK pathway 41 . Previous studies have demonstrated that ERK1/2 MAPK negatively regulates let-7 by inducing LIN28 expression through Myc transcription 42 .…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR was performed with SYBR Green Real-Time PCR Master Mix (Toyobo, Osaka, Japan) according to the manufacturer’s instructions. The qRT-PCR conditions for measuring mRNA levels in cerebellum tissues used in our laboratory have been reported previously [ 58 ]. The primers were as follows: occludin…”
Section: Methodsmentioning
confidence: 99%
“…hsa-miR-181b and hsa-miR-181d were found to be differentially expressed between invasive and non-invasive non-functional pituitary adenoma [ 61 ]. Finally, hsa-let-7c-5p facilitated enterovirus 71 replication through viral subversion of cell signaling in rhabdomyosarcoma cells [ 62 ].…”
Section: Resultsmentioning
confidence: 99%